2004
DOI: 10.1084/jem.20031916
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Stem Cells As an Alternate Marrow Donor Source

Abstract: A single embryonic stem cell (ESC) line can be repetitively cryopreserved, thawed, expanded, and differentiated into various cellular components serving as a potentially renewable and well-characterized stem cell source. Therefore, we determined whether ESCs could be used to reconstitute marrow and blood in major histocompatibility complex (MHC)-mismatched mice. To induce differentiation toward hematopoietic stem cells (HSCs) in vitro, ESCs were cultured in methylcellulose with stem cell factor, interleukin (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 34 publications
1
79
0
1
Order By: Relevance
“…As with other pluripotent stem cell-based gene therapy strategies targeting the hematopoietic system, the myeloprotective approach investigated here ultimately will require the generation of HSCs with in vivo long-term reconstituting potential (LT-HSCs), an aim that despite promising early data [48] has so far not been established as a reproducible procedure. Nevertheless, technological progress in recent years has considerably facilitated the in vitro generation of hematopoietic progenitor cells of various lineage commitments [49][50][51], and with foreseeable further advancement in this field, the generation of bona fide LT-HSCs from pluripotent cell sources appears as an achievable goal.…”
Section: Discussionmentioning
confidence: 99%
“…As with other pluripotent stem cell-based gene therapy strategies targeting the hematopoietic system, the myeloprotective approach investigated here ultimately will require the generation of HSCs with in vivo long-term reconstituting potential (LT-HSCs), an aim that despite promising early data [48] has so far not been established as a reproducible procedure. Nevertheless, technological progress in recent years has considerably facilitated the in vitro generation of hematopoietic progenitor cells of various lineage commitments [49][50][51], and with foreseeable further advancement in this field, the generation of bona fide LT-HSCs from pluripotent cell sources appears as an achievable goal.…”
Section: Discussionmentioning
confidence: 99%
“…Successful tolerance protocols would overcome alloresponses to donor islet alloantigens and could prevent recurrent autoimmunity in the donor islets, as suggested by mixed-chimaerism studies in NOD mice with advanced diabetes 39 . Either combined HSC and islets from deceased donors or the combined transplantation of embryonic stem cell 58 or adult stem-cellderived islets and HSC could ultimately be used to achieve tolerance and cure of type 1 diabetes. In addition, promising approaches to xenotolerance induction, including HCT 59 , might ultimately allow the use of xenotransplants (grafts from donors of other species such as pigs) that could provide a solution to the shortage of allogeneic islets.…”
Section: Future Directionsmentioning
confidence: 99%
“…For example, rat or mouse ES-derived hematopoietic cells can survive engraftment in a xenogenic or fully mismatched environment without immunosuppression. 55,66,67 This property may be due to the embryonic nature of ESCs, and seems to be conserved in hESCs. Li et al 68 have shown that hESCs and their derivatives can evade both in vivo xenogenic and in vitro allogeneic immune responses despite normal levels of MHCI.…”
Section: Rejection Of Allogenic Hescsmentioning
confidence: 99%
“…In addition, purifying cells can avoid complications due to the potential contamination of the graft with residual undifferentiated ESCs. For instance, in a study by Burt et al, 55 mESC-derived engraftable hematopoietic progenitors were shown to express c-kit + CD45 + cell-surface markers. The incidence of teratomas at the site of injection occurred only when whole, unsorted, cell populations were transplanted to irradiated mice, and not when fractionated c-kit + CD45 + were used.…”
Section: Purification Of Differentiated Cellsmentioning
confidence: 99%